Pengalihan Kewenangan Pemberian Izin Usaha Pertambangan Mineral-Batubara Oleh Pemerintah Daerah - Iqbal Shalihin (Faculty of Law, Andalas University, 2018)
With the enactment of Law Number 23 of 2014 on Regional Government, there is a change of authority between the central government, provincial and district governments. Article 4 paragraph (1) of the Law says that